Viva Texas Rivers! : Adventures, Misadventures, and Glimpses of Nirvana along Our Storied Waterways - Pfiester, Sam L. (Sam Lee); Davis, Steven L., 1963- (Book collections on Project MUSE., 2021)
"More than the lifeblood of our natural world, Texas rivers have nourished the human spirit for as long as people have gathered on their banks. A living bond has flowed between Texas writers and rivers ever since the 1960 publication of John Graves's classic journey along the Brazos, Goodbye to a River. Many of Texas' leading writers have had their hearts captured by a river, and they have created sparkling accounts of the waterways they love. Now, editors Steven L. Davis and Sam L. Pfiester have assembled the best of those works into a revelatory collection of diverse literary voices. Ranging from the desert canyonlands of the Rio Grande to the swampy Big Thicket, from crystal clear Hill Country streams to the Red River's treacherous quicksand, Viva Texas Rivers! showcases many classic writings along with brand new essays written for this volume. The literary nonfiction is complemented by flashes of poetry that brilliantly reflect these curving ribbons of light. Authoritative and expertly edited, Viva Texas Rivers! offers shimmering accounts of hidden paradises, as well as searing exposés of abuse and despoliation. Yet even in the bleakest times, as these writers have found, Texas rivers can bestow a sacred grace -- and unexpected redemption. Viva Texas Rivers! brings you as close to the living nirvana of a Texas River as you can get without launching yourself into a canoe and following a great blue heron as it glides just above the breaking rapids, leading you around the bend as the river flows onward toward the best places in our hearts"--Dust jacket.